2000
DOI: 10.1103/physrevlett.85.2168
|View full text |Cite
|
Sign up to set email alerts
|

Excitonic Effects in Core-Excitation Spectra of Semiconductors

Abstract: Core-electron excitation spectra are used widely for structural and chemical analysis of materials, but interpretation of the near-edge structure remains unsettled, especially for semiconductors. For the important Si L(2,3) edge, there are two mutually inconsistent interpretations, in terms of effective-mass excitons and in terms of Bloch conduction-band final states. We report ab initio calculations and show that neither interpretation is valid and that the near-edge structure is in fact dominated by short-ra… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

2
76
0
2

Year Published

2005
2005
2023
2023

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 96 publications
(80 citation statements)
references
References 30 publications
2
76
0
2
Order By: Relevance
“…EELS O K-edge fine structure simulations were performed using the Z + 1 approximation [17,18]. The calculations were carried out using DFT [22,23] in the generalized-gradient approximation and using the projector-augmented-wave method [24] with a plane-wave basis as implemented in the Vienna ab initio simulation package (VASP) code [25].…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…EELS O K-edge fine structure simulations were performed using the Z + 1 approximation [17,18]. The calculations were carried out using DFT [22,23] in the generalized-gradient approximation and using the projector-augmented-wave method [24] with a plane-wave basis as implemented in the Vienna ab initio simulation package (VASP) code [25].…”
Section: Methodsmentioning
confidence: 99%
“…EELS spectra show the O K-edge fine structure from inside the YSZ of coherent YSZ/STO multilayers to be blurred out, in contrast to the sharp features seen in bulk YSZ. DFT simulations of the O K-edge fine structure using the Z + 1 approximation [17,18] confirm that the blurred out fine structure can be attributed to O sublattice disorder. In addition, we report atomic-resolution EELS elemental maps taken across the YSZ-STO interface, in which the O columns of STO are seen to blur out to the point of randomness in the strained YSZ.…”
Section: Introductionmentioning
confidence: 99%
“…In our following analysis, the energy point of the half-way maximum of the first XAS band is used as the CBM estimate. This treatment of the XAS accounts for the existence of a core-excitonic state within the XAS edge [22] in contrast to the expected smooth onset of the conduction-band DOS (see CB DOS in Figure 1). This coreexcitonic state leads to an excitonic screening-energy contribution in the CBM which can be estimated in our band gap analysis as well.…”
Section: Band-gap Analysis From Xas and Rixsmentioning
confidence: 99%
“…This coreexcitonic state leads to an excitonic screening-energy contribution in the CBM which can be estimated in our band gap analysis as well. Note that Buczko et al discussed the effect of the core hole exciton for the Si 2p spectrum of silicon [22]. They concluded that a calculation that uses an extra core charge (Z+1 approximation) or even a Bethe-Salpeter Equation (BSE) calculation, which includes both the core-hole and the excited electron in a neutral transition, is required for a simulation that fits onto experimental XAS.…”
Section: Band-gap Analysis From Xas and Rixsmentioning
confidence: 99%
“…The thresholds of x-ray absorption due to deep core levels were measured and compared with calculations, since the thresholds are good indexes for identification of atomic species and environment of the atoms or ions. The excitonic effect on the thresholds was disputed for a long time before it was accepted [7]. Shallow core excitons that consist of an outermost core hole and a conduction electron are clearly observed in optical reflectivity spectra of various substances [8,9].…”
mentioning
confidence: 99%